U0126 Attenuates Cerebral Vasoconstriction and Improves Long-Term Neurologic Outcome after Stroke in Female Rats. Issue 3 (March 2015) - Ahnstedt, Hilda; Mostajeran, Maryam; Blixt, Frank W; Warfvinge, Karin; Ansar, Saema; Krause, Diana N; Edvinsson, Lars
Sex differences are well known in cerebral ischemia and may impact the effect of stroke treatments. In male rats, the MEK1/2 inhibitor U0126 reduces ischemia-induced endothelin type B (ETB ) receptor upregulation, infarct size and improves acute neurologic function after experimental stroke. However, responses to this treatment in females and long-term effects on outcome are not known. Initial experiments used in vitro organ culture of cerebral arteries, confirming ERK1/2 activation and increased ETB receptor-mediated vasoconstriction in female cerebral arteries. Transient middle cerebral artery occlusion (tMCAO, 120 minutes) was induced in female Wistar rats, with U0126 (30 mg/kg intraperitoneally) or vehicle administered at 0 and 24 hours of reperfusion, or with no treatment. Infarct volumes were determined and neurologic function was assessed by 6-point and 28-point neuroscores. ETB receptor-mediated contraction was studied with myograph and protein expression with immunohistochemistry. In vitro organ culture and tMCAO resulted in vascular ETB receptor upregulation and activation of ERK1/2 that was prevented by U0126. Although no effect on infarct size, U0126 improved the long-term neurologic function after experimental stroke in female rats. In conclusion, early prevention of the ERK1/2 activation and ETB receptor-mediated vasoconstriction in the cerebral vasculature after ischemic stroke in female rats improves the long-term neurologic outcome.